Risque climatique et réactivité des populations urbaines vulnérabilisées face à la montée des eaux de mer à Gonzagueville, Abidjan (Côte d’Ivoire) - Chérif Sadia (VertigO, 2014)
From August, 24th to 26th 2011, sea rose to heights superior to 2 m causing damage to property and migration of populations of the coastal district of Gonzagueville in Abidjan. Press in Côte d’Ivoire raised the exclusive character of these events. But, they are connected to the global environmental changes which exercise an additional pressure on the coastal zone of port cities such Abidjan. The socio-spatial organization of the city of Abidjan highlights the vulnerability of the poor populations of Gonzagueville which occupy the coastal parts and are in the front line at the time of sea level rise. However, their capacity of reaction allows finding local solutions in the undergone phenomenon. To understand this process, informal inquiries were led with the victims of sea level rise of Gonzagueville coupled with direct observation and a local press review. As such, the resilience process of the victims of Gonzagueville declines in several phases follow-up of the expression of the generosity of the authorities towards them. Spontaneity of that form of resilience leads to a recurring exposure at the risk and is little effective in front of uncertainties in the assessment of risks connected to the nowadays global environmental changes. For that purpose, the article proposes rather the preventive resilience consisting of measures to prevent risks incurred by the Abidjan’s populations.